Analysis of the Effect of Occupational Safety and Health (K3) on Employee Performance in Distribution Center Area Logistics Division - Abdul Rohim; Farida Hardaningrum (NAROTAMA UNIVERSITY, Indonesia, 2022)
In Indonesia, problems related to Occupational Safety and Accidents (K3) are still quite large, both in cities and in villages, both in the industrial and service sectors as well as in the agricultural sector. This is evident from the still high number of work accidents that occur. Throughout 2020, work accidents in Indonesia reached 153,044 cases, where this figure decreased by 1.46 percent when compared to work accident cases in 2019, which was 155,327 cases. The purpose of this study was to determine the effect of occupational safety and health on the performance of employees of the Logistics Division of PT. Indomarco Prismatama Gresik Branch. Data was collected through the distribution of questionnaires, with the number of respondents as many as 60 employees of the Logistics Division of PT. Indomarco Primatama Gresik Branch. The sampling technique used is random sampling using questionnaires and data testing techniques used in this study include validity and reliability tests, multiple regression analysis tests, F tests, and t tests. The results of this study indicate that: (1) work safety has a positive effect on employee performance; (2) occupational health has a positive effect on employee performance; and (3) occupational safety and health affect employee performance.